2015
DOI: 10.1007/s11299-015-0168-x
|View full text |Cite
|
Sign up to set email alerts
|

Models of complex adaptive systems in strategy and organization research

Abstract: The development of new theory is often spurred by novel techniques that provide better answers to existing questions, or that allow asking new ones. In the field of strategy and organization science, models of complex adaptive systems have renewed theoretical work on a fundamental question: how organizations can adapt effectively to their environments. This article has three objectives: (1) to highlight some areas where models of organizations as complex adaptive systems have made substantial contributions: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…A second set of reviews deals with the models that underlie research on complexity and search. Baumann (2015) and Ganco and Hoetker (2009) provide more technical summaries of the NK model, including its assumptions and underlying mechanisms. Porter and Siggelkow (2008) provide an overview of the NK model and the complementarity framework from economics as two modeling approaches to capture interdependencies.…”
Section: More Broadly We Argue That Important Insights Can Be Gainedmentioning
confidence: 99%
“…A second set of reviews deals with the models that underlie research on complexity and search. Baumann (2015) and Ganco and Hoetker (2009) provide more technical summaries of the NK model, including its assumptions and underlying mechanisms. Porter and Siggelkow (2008) provide an overview of the NK model and the complementarity framework from economics as two modeling approaches to capture interdependencies.…”
Section: More Broadly We Argue That Important Insights Can Be Gainedmentioning
confidence: 99%
“…While computer scientists are primarily interested in finding the optimal solution to learning problems, organization scientists have focused on the descriptive value of learning models. In particular, learning problems in organizations have often been described within the learning by doing framework and modelled using reinforcement learning tasks (e.g., [11,[24][25][26][27][28][29]; see [30] for a review). is is because organizational learning problems frequently meet the two conditions that define reinforcement learning problems.…”
Section: Learning By Doing As a Form Of Reinforcement Learningmentioning
confidence: 99%
“…Based on the work of Benz (2007) and Heinze and Kuhlmann (2007), various institutes conducting research in different fields are found to need a balance between cooperation and competition with other partner institutes under the same umbrella and with external research institutes. Additionally, there is another typical mediation situation at L2 (March, 1991;Baumann, 2015)-the choices between exploration of new research directions, institutes, programmes, and exploitation of the current resources. All the above hypothetical tensions are explored in the case studies of MPG, HGF, and CAS.…”
Section: The Enriched Conceptual Framework On the Role Of Evaluation mentioning
confidence: 99%